2010
DOI: 10.1590/s1415-43662010001100006
|View full text |Cite
|
Sign up to set email alerts
|

Inoculação de variedades locais de feijão macassar com estirpes selecionadas de rizóbio

Abstract: RESUMOA combinação eficiente entre variedades e estirpes de rizóbio é importante para aumentar a produtividade do feijão macassar; entretanto, estirpes selecionadas não foram testadas com a maioria das variedades cultivadas na região semiárida do Nordeste do Brasil. Com o objetivo de avaliar a eficiência de quatro estirpes recomendadas de rizóbio em seis variedades de feijão macassar cultivadas no Agreste da Paraíba, conduziu-se um experimento fatorial em blocos casualizados com três repetições, em vasos de Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
3
4
0
3
Order By: Relevance
“…In the second reading, held at the beginning of the pods maturation, R3 stage, the SPAD index was not significant because many leaves had already lost its original chlorophyll content or had even suffered abscission ( Figure 1B). The results observed in the R1 stage corroborate with Vieira et al (2010), who reported that the treatments fertilized with nitrogen gave the largest increments of nitrogen in plants.…”
Section: Resultssupporting
confidence: 89%
“…In the second reading, held at the beginning of the pods maturation, R3 stage, the SPAD index was not significant because many leaves had already lost its original chlorophyll content or had even suffered abscission ( Figure 1B). The results observed in the R1 stage corroborate with Vieira et al (2010), who reported that the treatments fertilized with nitrogen gave the largest increments of nitrogen in plants.…”
Section: Resultssupporting
confidence: 89%
“…Although no inoculation effect was observed at plant height, Furlan et al (2016) observed that inoculation treatments promoted increments in height and diameter of snap beans, as well as improving other agronomic characteristics. Vieira et al (2010) found a similar result for the dry mass of aerial part (DMAP), with a difference between the accumulations of biomass among six Macassar bean cultivars, not observing a significant effect of DMAP increase as a function of inoculation. However, Fonseca et al (2013), in addition to finding differences between common bean cultivars, observed higher DMAP in inoculated plants, attributing to the fact the greater efficiency of inoculated strains in providing nitrogen to the bean, with increases of 15 to 20% in the biomass.…”
Section: Resultssupporting
confidence: 54%
“…Pôde-se constatar, também, que a cultivar BRS Guariba promoveu, na média geral, ANPA (142,82 mg planta -1 ) significativamente (p<0,05) superior à BR 17 Gurgueia (123,90 mg planta -1 ) (Tabela 2). De acordo com esses resultados podese inferir que as cultivares de feijão-caupi avaliadas, além de responderem de maneira diferenciada à inoculação com estirpes de rizóbios, apresentam diferentes potenciais na FBN, fato também constatado em outros trabalhos (Xavier et al, 2006;Belane & Dakora, 2009;Vieira et al, 2010 Quanto à eficiência nodular (EFNOD), a interação entre os fatores não foi significativa (p>0,05), porém houve efeito individual dos tratamentos e cultivares (Tabela 3).…”
Section: Resultsunclassified